A case of lymphomatosis cerebri mimicking inflammatory diseases. Issue 1 (December 2016) - Murakami, Takenobu; Yoshida, Kenji; Segawa, Mari; Yoshihara, Akioh; Hoshi, Akihiko; Nakamura, Koichiro; Ichikawa, Masahiro; Suzuki, Osamu; Yokoyama, Yuichi; Toyoshima, Yasuko; Sugiura, Yoshihiro; Ito, Hiroshi; et al.
Abstract Background Lymphomatosis cerebri (LC) is a rare subtype of primary central nervous system malignant lymphoma. The typical features of this disease exhibited on magnetic resonance imaging (MRI) without contrast enhancement are similar to those observed with diffuse leukoencephalopathy, mimicking white matter disorders such as encephalitis. Clinical features and examination findings that are suggestive of inflammatory diseases may indeed confound the diagnosis of LC. Case presentation A 66-year-old woman with continuous fever over a two-month period developed left hemiparesis despite presenting in an alert state with normal cognitive function. Sampling tests showed autoantibodies in the serum and inflammatory changes in the cerebrospinal fluid. The results from an MRI demonstrated multiple non-enhanced brain lesions in the splenium of the corpus callosum and deep white matter. Single photon emission computed tomography revealed increases in blood flow in the basal ganglia, thalamus and brainstem. No systemic malignancies were found. The patient was suspected of having a diagnosis of nonvasculitic autoimmune inflammatory meningoencephalitis and treated with intravenous methylprednisolone pulse therapy. Her fever transiently dropped to within the normal range. However, she had a sudden seizure and a second MRI exhibited infiltrative lesions gradually extending throughout the whole brain. We performed a brain biopsy, and LC was histologically diagnosed. The patient received whole-brain radiation therapy, which diminished the fever and seizures. The patient died one year after the initial onset of fever. Conclusions The present case yields an important consideration that brain neoplasms, especially LC, cannot be ruled out, even in cases with clinical characteristics and examinations consistent with inflammatory diseases. Careful follow-up and histological study are vital for the correct diagnosis of LC.